Advances in Multimedia Modeling 19th International Conference, MMM 2012, Huangshan, China, January 7-9, 2012, Proceedings, Part II - Li, Shipeng; El Saddik, Abdulmotaleb; Wang, Meng; Mei, Tao; Sebe, Nicu; Yan, Shuicheng; Hong, Richang; Gurrin, Cathal (Information Systems and Applications, incl. Internet/Web, and HCI, 2013)
The two-volume set LNCS 7732 and 7733 constitutes the thoroughly refereed proceedings of the 19th International Conference on Multimedia Modeling, MMM 2012, held in Huangshan, China, in January 2013. The 30 revised regular papers, 46 special session papers, 20 poster session papers, and 15 demo session papers, and 6 video browser showdown were carefully reviewed and selected from numeroues submissions. The two volumes contain papers presented in the topical sections on multimedia annotation I and II, interactive and mobile multimedia, classification, recognition and tracking I and II, ranking in search, multimedia representation, multimedia systems, poster papers, special session papers, demo session papers, and video browser showdown.